Teachers' evaluation on the participation of animals in teaching activities of Experimental Behavior Analysis in Brazil (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The participation of animals in the teaching of Experimental Behavior Analysis (EAB) is a well-established tradition that has been challenged due to critical assessments, legislative changes, and high expenses that affect such practices. In this study, we investigate the evaluation that EAB teachers make of the participation of animals in EAB teaching activities in Brazil. Sixty-one teachers participated in the study. The majority (86.9%) taught classes after the regulation of the current legislation, included animals in their practical activities (57.4%), preferred practices with the participation of animals (67.2%) mainly due to the understanding that the alternative practices available are not adequate to replace animals. Most respondents (97.0%) used the national manuals as a primary bibliography. However, it is common to present objectives that are not justifiable or insufficient for the participation of animals in these practices. It is suggested that it is necessary to train better EAB teachers that include animals, and develop and evaluate better alternative methods.